Properties of the silver cyclic amide Ag-2(C4H4NO2)(2)(H2O) crystal from the periodic DFT computations - Stashans, A. (2017)
A molecular crystal of silver cyclic amide Ag-2(C4H4NO2)(2)(H2O) is studied using first-principles density functional theory calculations within the generalized gradient approximation (GGA). A number of different exchange-correlation functionals are considered for a possible treatment of the system. It is found that the Perdew-Burke-Ernzerhof (PBE) GGA exchange-correlation functionals are adequate for the Ag-2(C4H4NO2)(2)(H2O) crystal. The results obtained show the possibility to reproduce rather well the geometry of at least some molecular crystals by means of the periodic solid-state calculations if the computational parameters are chosen adequately. The present work also reports the analysis of the chemical bonding in the material and gives the total and partial density of states. Our solid-state computations point out the possible magnetic properties of the molecular crystal under study.